IMPLEMENTASI FAILOVER MENGGUNAKAN JARINGAN VPN DAN METRONET PADA ASTRIDOGROUP INDONESIA - Agni Isador Harsapranata (CCIT Journal, 2015)
The purpose of this research is to build a network that connects the head office and branch offices Astridogroup Indonesia, with the hope of the entire performance can be improved connections to support business objectives. To meet these needs and the failures of communication technology that was used, in which the technology is to use a connection that can always be online in the hope of quality of service close to 100%. The technology used is to use two connection lines, the first is to use optical fiber Metronet, and the second VPN using wifi internet, so that if one connection dies , the another connection would be a backup, to set both the connection failover using mikrotik router.